The preterm gut microbiota and administration routes of different probiotics: a randomized controlled trial - Rahkola, Ella-Noora (My University, 2023)
Preterm children are prone to several health problems which may partly be because of their aberrant gut microbiota. Probiotics, which are living bacteria with assumed health benefits, could be used to modify the preterm gut microbiota towards the composition of the healthy term children’s gut microbiota which is rich in bifidobacteria. It is not yet known what the most effective and safest probiotic supplement and its administration route would be. It has been hypothesized that the maternal administration route via breast milk could be safer. In this trial, the maternal and direct oral administration route of two different probiotics (Lactobacillus rhamnosus GG (LGG) with or without Bifidobacterium lactis Bb-12 (Bb12)) were compared by randomizing 68 preterm neonates with their mothers into five intervention groups to receive the probiotic supplement beginning from the median age of 3 days. One of the groups received placebo. The children’s faecal microbiota at the age of 7 days was assessed by 16s rRNA gene sequencing. At the age of 7 days, The gut microbiota compositions of the children who directly received the probiotic combination (LGG + Bb12) were significantly different from those of the children receiving the other intervention modes or placebo. The distinction was due to an increase in the relative abundance of Bifidobacterium animalis and the order Lactobacillales. Therefore, it was shown that the direct, early, and brief probiotic intervention with LGG + Bb12 was sufficient to modulate the preterm microbiota whereas the maternal route was not as effective.
Keywords: keskonen, probiootti, suolistomikrobisto